POSIBILITIES OF THE OBSERVATIONAL METHODOLOGY IN THE ANALYSIS OF CLASSROOM BEHAVIORS: APPLICATION IN STUDENTS WITH BEHAVIOR PROBLEMS - Herrero, María Luisa (Anales de Psicología / Annals of Psychology)
In this work we seek to make a study -by the systematic observaton and by the secuencial data analysis with the delay technique- of children showing behavioral and relationship problems in the classroom, in order to analyze and determine behaviours and interactons of these children with theirs similars and with adults, to establish a suitable and rigorous plan to guide and follows these children in teh school level and it the familiar one.